Impaired patient-reported outcomes but preserved gait patterns 5–15 years after acetabular fracture compared with healthy controls - Fensel-Merz, Selma; Warmerdam, Elke; Orth, Marcel; Pohlemann, Tim; Liodakis, Emmanouil; Ganse, Bergita (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionLittle is known about the long-term subjective patient experience after acetabular fracture and its relationship with changes in gait patterns. Worse outcomes were hypothesized compared with healthy control participants.MethodsPatient-Reported Outcome Measure Information System (PROMIS) questionnaires and treadmill-based gait analyses were conducted. Twenty parameters derived from the ground-reaction force curve were analysed. One-way ANOVA, Mann‒Whitney U tests, and regression statistics were used to assess differences between patients and controls (26 participants) and correlations between PROMIS scores and gait parameters.ResultsTwenty-six patients (19 men and 7 women, 52.09 ± 12.77 years) with previous acetabular fracture an average of 9.90 ± 2.97 years prior to the study were included, all with excellent or good quality of reduction. While significantly worse results were found in the fracture than in the control group for all tested PROMIS scores (Physical Health, p < 0.001; Mental Health, p < 0.001; Pain Interference, p = 0.011; Physical Function, p < 0.001), no changes were observed in the gait parameters. There was no correlation between the PROMIS scores and any of the gait parameters. Forty-six percent of patients reported occasional pain and twelve percent noted weather sensitivity.DiscussionFactors other than changes in gait pattern seem to cause worse PROMIS scores in patients after acetabular fracture.